Features of Business Administration at different stages of Enterprise Life Cycle - Solokha, Dmytro; Bessonova, Svitlana; Makarenko, Maryna; Redkin, Oleksandr (International Journal of Engineering and Technology, 2018)
The purpose of the study is to formulate an approach to business administration based on the definition of the appropriate stage of enterprise life cycle. The proposed approach complements the existing methods by combining both the evaluation Â based on the analysis of characteristics of the internal components of the enterprise and the evaluation of the level of competitiveness of the enterprise and the level of financial and economic activity. The analysis of literature in the field of the theory of the enterprise life cycleÂ has allowed to form a generalized five-stage model of ELC, which includes the stages of formation, development, maturity, diversification and decline. It has been substantiated that the machine-building enterprises in Ukraine, depending on the internal contextual variables, came to such stages of the life cycle as development, maturity, and diversification. At the first stage of development, the company has a simple structure, small size and low level of formalization. At the second stage, companies are barely older and bigger, use more complex types of organizational structures and more formalized. At the third stage, enterprises are even larger and older, have a higher level of formalization and a complex structure, which periodically varies. Indicators determining the level of financial and economic activity and competitiveness of the enterprise considerably increase the accuracy of the definition of the stage of the enterprise life cycle. According to the indicators, it is possible to draw a conclusion about the degree of efficiency of the enterprise at different stages of the life cycle. Therefore, in order to choose the appropriate direction of activity, strategy for the development of an industrial enterprise, or the method of decision-making, it is necessary to monitor various financial and economic indicators and indicators of competitiveness that will determine the stage of the enterprise life cycle.Â Â Â